The Oxford handbook of Islamic law - Emon, Anver M.; Ahmed, Rumee (Oxford handbooks., 2018)
This volume provides a comprehensive survey of the contemporary study of Islamic law and a critical analysis of its deficiencies. Written by outstanding senior and emerging scholars in their fields, it offers an innovative historiographical examination of the field of Islamic law and an ideal introduction to key personalities and concepts. 0While capturing the state of contemporary Islamic legal studies by chronicling how far the field has come, the Handbook also explains why certain debates recur and indicates fundamental gaps in our knowledge. Each chapter presents bold new avenues for research and will help readers appreciate the contested nature of key concepts and topics in Islamic law. This Handbook will be a major reference work for scholars and students of Islam and Islamic law for years to come.